Warriors : all the truth, tactics, and triumphs of history's greatest fighters - Harpur, James (New York : Atheneum, 2007)
Highlights celebrated warriors and soldiers from all periods of history.
Features pull-outs and fold-out pages.
One col. folded ill. in pocket.
Includes bibliographical references (inside back cover).
Keywords: Military history -- Juvenile literature; Military art and science -- History -- Juvenile literature; Soldiers -- History -- Juvenile literature; Toy and movable books